Efficacy of a public promotion program on children's oral health - Ana Paula S. Alves; Rise C.I.C. Rank; Joana Estela R. Vilela; Marcos S. Rank; Wataro N. Ogawa; Omar F. Molina (Elsevier, 2018)
Objective: To assess the efficacy of the Baby's Mouth early dental care prevention and promotion program in preventing oral diseases (caries, gingivitis, or malocclusions) in children attended since 2010. Methods: This was a cross-sectional and cohort study that assessed 252 children between 36 and 60 months of age in both sexes. The children were divided into three groups: G1: effective participants of the program from birth; G2: children who have stopped participating for more than 24 months, and G3: children who have never attended a prevention program. The evaluation was carried out in two stages: first, an interview with the mothers and, afterwards, a clinical children examination to assess the presence of caries, gingivitis, and malocclusion. The chi-squared test was used for statistical analysis between groups (p < 0.05). Results: The diseases assessed were: caries (G1: 5.9%, G2: 54.7%, G3: 70%), gingivitis (G1: 8.3%, G2: 17.9%, G3: 40.5%), and malocclusion (G1: 22.6%; G2: 28.6%; G3: 50%). For gingivitis, there was no significant difference when comparing G1 and G2 (p = 0.107), but it was significant between G1 and G3 (p < 0.001). Regarding malocclusion, a statistically significant relationship was observed (p = 0.004) among all groups. Conclusion: The prevention and promotion program in public oral health was effective in preventing caries disease, gingivitis, and malocclusion in children under 5 years of age. Resumo: Objetivo: Avaliar a eficácia do programa de prevenção e promoção de cuidados dentários precoce da boca do bebê, a fim de prevenir doenças bucais (cáries, gengivite ou má oclusões) em crianças atendidas desde 2010. Métodos: Estudo transversal e de coorte com avaliação de 252 crianças entre 36 e 60 meses de idade de ambos os sexos. As crianças foram divididas em dois grupos: G1: participantes efetivos do programa a partir do nascimento; G2: crianças que pararam de participar por mais de 24 meses do programa; e G3: crianças que nunca participaram de um programa de prevenção. A avaliação foi feita em dois estágios: entrevista com as mães e, depois, um exame clínico nas crianças para analisar cáries, gengivite e oclusão. Foi utilizado o teste qui-quadrado para análise estatística entre os grupos (p < 0,05). Resultados: As doenças analisadas foram: cáries (G1: 5,9%, G2: 54,7%, G3: 70%), gengivite (G1: 8,3%, G2: 17,9%, G3: 40,5%) e má oclusão (G1: 22,6%; G2: 28,6%; G3: 50%). Para gengivite, não houve diferença significativa ao comparar G1 e G2 (p = 0,107), porém a diferença foi extremamente significativa entre G1 e G3 (p < 0,001). Nas oclusões, houve uma relação estatisticamente significativa (p = 0,004) entre todos os grupos. Conclusão: O programa de prevenção e promoção de saúde bucal pública foi efetivo na prevenção de cáries, gengivite e má oclusão em crianças com menos de cinco anos de idade. Keywords: Pediatric dentistry, Primary prevention, Oral health, Dental caries, Public health, Palavras-chave: Odontopediatria, Prevenção Primária, Saúde bucal, Cáries dentárias, Saúde Pública